2017
DOI: 10.26417/ejms.v5i1.p158-164
|View full text |Cite
|
Sign up to set email alerts
|

Headmaster’s Competencies in Management Area: Evaluating the Significance Level of Managerial Competencies in Lithuanian Comprehensive Schools

Abstract: The aim of the article is to present the insights of carried survey on evaluating the level of significance of managerial competencies in comprehensive schools in Lithuania. The approach that head teachers' managerial competency highly influences the process of education and is one of the most important factors ensuring efficiency of school activities such as educational policy and strategic planning, educational process, management of human, material and financial resources has been followed. Researcher self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
0
6
0
2
Order By: Relevance
“…Faktor utama yang memegang peranan penting meningkatkan kualitas sekolah, inisiator dan motor penggerak pengembangan lembaga pendidikan adalah kepala sekolah (Bairašauskienė, 2017). Permendiknas no.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Faktor utama yang memegang peranan penting meningkatkan kualitas sekolah, inisiator dan motor penggerak pengembangan lembaga pendidikan adalah kepala sekolah (Bairašauskienė, 2017). Permendiknas no.…”
Section: Pendahuluanunclassified
“…13 tahun 2007 menjabarkan tentang standar kepala sekolah dua diantaranya mengembangkan organisasi sekolah/ madrasah sesuai kebutuhan dan mengelola perubahan dan pengembangan sekolah/ madrasah menjadi organisasi pembelajar yang efektif. Namun pada kenyataannya belum semua kepala sekolah memenuhi standar kompetensi yang seharusnya dikuasai kepala sekolah (Bairašauskienė, 2017). Sementara pada sisi lain berdasarkan training need assessment yang dilakukan, memiliki keterbatasan dalam sumber daya dana, kemampuan dan fasilitas pendukung untuk meningkatkan kompetensi kepala sekolah (Firdaus & Jember, 2017).…”
Section: Pendahuluanunclassified
“…Management of improving the quality of education is a method of improving quality that relies on the institution itself, applying a collection of techniques, basing on the availability of quantitative and qualitative data and empowering all components of educational institutions to continuously increase capacity and the ability of the organization to meet the needs of students and society (Bush, Bell, & Middlewood, 2019;Chan, 2018;Baharudin, 2017;Cajiao, & Burke, 2016). So it can be concluded that the quality of education needs good management from all aspects, especially from head management, teacher management, learning curriculum management, infrastructure and school financialmanagement (Jamli, 2019;Bairaðauskienë, 2017;Böhlmark, Grönqvist, & Vlachos, 2016).…”
Section: Management Of Education Quality Improvementmentioning
confidence: 99%
“…Management functions have to be implemented in the organization and should become the benchmark of the success of an organization in running the activities including in the school organization (Bairaðauskienë, 2017;Böhlmark, Grönqvist, & Vlachos, 2016). As a formal education institution, a school is a spearhead in educating children to create the generations that reliable and competitive, considering Indonesia will have a demographic bonus in the next few years which is a good chance in advancing the country.…”
Section:  Introductionmentioning
confidence: 99%